Numerical Studies to Predict the Impact of Air Nozzle Position and Inclination on the Performance of Downdraft Gratifier - P. C. Murugan (Journal of Applied Fluid Mechanics, 2017)
Biomass gasification is one of the promising technologies to produce energy from the renewable energy sources, and the downdraft biomass gasifier is a widely used biomass energy conversion device. Among the various components of a gasifier, the position and the inclination of air nozzle have a vital role in the generation of producer gas. Therefore, a proper design is needed to fix the position and angle of the air nozzle. Keeping the above aspects, the present work focuses on the numerical simulation to predict the appropriate position and inclination of the air nozzle in a 50kWth imbert type downdraft gasifier by the species transport approach. The nozzle inclination varies from 0°, 20°, 30°, 45° and 60°, and the nozzle position is considered from 50mm, 100mm, 150mm and 200mm respectively. Experiments were also conducted to validate the numerical study. Both the studies show that the nozzle inclination at 45° and its position at 100mm above the reduction zone gives a reasonable composition of producer gas.